2008
DOI: 10.1021/om701149f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cis and Trans Ligands in Platinum(II) Complexes on the Ability of the Platinum Center to Activate C−H Bonds. A Density Functional Theory Study

Abstract: We have studied the influence of different ligands X (X ) F, Cl, Br, I, NO 2 , and CN) on the C-H bond activation of CH 4 in trans-PtCl 2 X(CH 4 ) -, 1, and trans-PtClX 2 (CH 4 ) -, 2, where X is either trans (1) or cis (2) to methane. For 1 with X in the trans position, the trans-PtCl 2 Xfragment interacts with CH 4 through the overlap between the empty d σ -based orbital 2a 1 pointing along the Pt-X direction and σ CH on CH 4 . An interaction also takes place between an occupied d σ -based orbital 1b 1 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Extensive kinetic and thermochemical studies 1–17 on square planar complexes of d 8 metals (M = Ni, Pd, Pt) have revealed that the ML bond strength strongly depends on the trans‐ligand T (trans influence) as does the barrier of substitution of L by another ligand Y (trans effect) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive kinetic and thermochemical studies 1–17 on square planar complexes of d 8 metals (M = Ni, Pd, Pt) have revealed that the ML bond strength strongly depends on the trans‐ligand T (trans influence) as does the barrier of substitution of L by another ligand Y (trans effect) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…3 Very often the trans influence has been invoked in organometallic chemistry to explain several reaction pathways. [13][14][15][16][17][18][19][20][21][22][23][24] This influence is not only significant in transition metal complexes and p-block metal compounds, 25-27 but also plays a major role in the stability of hypervalent aryl l 3 -iodanes. 28 Though a number of experimental studies are available, 6,8,29-31 theoretical investigations of trans influence 32-38 are comparatively less.…”
Section: Introductionmentioning
confidence: 99%
“…11 For this reason, computational quantum chemistry tools may conveniently be used to investigate the atomistic details of C-H activation. Indeed, several theoretical studies focused on Shilov 12,13 and Shilov-type [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] reactions (see e.g. ref.…”
mentioning
confidence: 99%